Recent Advances in Plant-Based, Traditional, and Natural Medicines 2014
DOI: 10.1201/b16611-7
|View full text |Cite
|
Sign up to set email alerts
|

The Relevance of Traditional Knowledge Systems for Ethnopharmacological Research: Theoretical and Methodological Contributions

Abstract: Background: Radix notoginseng is used in Chinese medicine to improve blood circulation and clotting; however, the pharmacological activities of other parts of Panax notoginseng have yet to be explored. The present study reports the anti-oxidative effects of various parts of Panax notoginseng. Methods: Various parts of Panax notoginseng, including the biennial flower, stem-leaf, root-rhizome, fiber root and sideslip, were used to prepare extracts and analyzed for their anti-oxidation effects, namely suppressing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Methanol and water are the most common solvents to extract the bioactive compounds of herbal medicines for LC analysis and traditional decoction, respectively. Previous study indicated that water extract of PNF showed the stronger anti‐oxidative effects than ethanol extracts . Our preliminary studies also demonstrated that HPLC–UV profiles of PNF or P. notoginseng leaves extracted by water and methanol were markedly different.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…Methanol and water are the most common solvents to extract the bioactive compounds of herbal medicines for LC analysis and traditional decoction, respectively. Previous study indicated that water extract of PNF showed the stronger anti‐oxidative effects than ethanol extracts . Our preliminary studies also demonstrated that HPLC–UV profiles of PNF or P. notoginseng leaves extracted by water and methanol were markedly different.…”
Section: Introductionsupporting
confidence: 60%
“…P. notoginseng flower (PNF), as folk medicine or diet supplement, exhibited various pharmacological activities, including anti‐colorectal cancer , anti‐microbial activity , anti‐oxidation , anti‐inflammation , hepatoprotective effect , and ameliorative effect on acute myocardial infarction . PNF contains the highest abundance of saponins among the different parts of P. notoginseng , but the saponin composition of flower is distinctly different to the roots .…”
Section: Introductionmentioning
confidence: 99%
“…The compounds in the composition were shown to be capable of targeting the hallmarks of AMD, including oxidative stress, RPE cytotoxicity, inflammation and vascular edema (5). The composition contains raw materials from herbs that can eliminate inflammation (25)(26)(27)(28)(29)(30), modulate immunity (31)(32)(33)(34)(35)(36)(37), promote blood circulation in order to remove blood stasis (38,39), prevent bleeding (40,41) and promote the absorption of macular exudates, edema and hemorrhage, as well as reduce the leakage and area of CNV (42). Treatment with the composition was found to enhance and stabilize the vision of patients with AMD, while the CNV leakage was more significantly reduced compared with Avastin ® treatment (anti-VEGF agent) (5).…”
Section: Discussionmentioning
confidence: 99%
“…There were few reports showing the preventive effects of sesaminol on impaired cells. Oxidative damage of rat pheochromocytoma (PC12) cells induced by H 2 O 2 is usually used as in vitro model to estimate the antioxidative activity of antioxidants because PC12 cells are more sensitive to oxidants than other cells and easy to set up an oxidative cell model. Thus, in the present study, we try to investigate the antioxidant effects of sesaminol on H 2 O 2 ‐injured PC12 cells.…”
Section: Introductionmentioning
confidence: 99%